2003
DOI: 10.3353/omp.8.43
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma in-situ of the Oral Mucosa has a Definite Tendency towards Keratinization.

Abstract: and Saku T. Carcinoma in-situ of the oral mucosa has a definite tendency towards keratinization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Such a well‐differentiated tendency is widely considered to be characteristic of oral SCC. Then why is this not the case for oral CIS? 12 Almost half of the surgical margins with CIS ranging from the basaloid to acanthotic types, were shown to develop into SCC. These retrospective data indicates that there were definite numbers of such well‐differentiated types in oral CIS, in addition to authentic basaloid CIS 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a well‐differentiated tendency is widely considered to be characteristic of oral SCC. Then why is this not the case for oral CIS? 12 Almost half of the surgical margins with CIS ranging from the basaloid to acanthotic types, were shown to develop into SCC. These retrospective data indicates that there were definite numbers of such well‐differentiated types in oral CIS, in addition to authentic basaloid CIS 5 .…”
Section: Discussionmentioning
confidence: 99%
“…This is because it is not easy to follow individual cases of dysplasia until they develop into frankly invasive carcinomas and also because some cases of dysplasia have been known to be self‐regressive 8 . We have noted the characteristic two‐phase appearance of epithelial dysplasia, which is frequently found in the periphery of invasive carcinoma or CIS and reasonably considered to be related to malignancy 9–13 . Based on topography we have also proposed that oral CIS has a definite tendency towards keratinization, because non‐invasive but obviously atypical epithelial lesions in the vicinity of invasive carcinoma foci tend to be keratinized 12 .…”
mentioning
confidence: 96%
“…From our observation in this study that this particular form of epithelial dysplasia is frequently observed in the vicinity of severe dysplasia/carcinoma in situ , it is suggested that the basaloid cells proliferate focally in the lower layer of the epithelium and then replace the whole layer to become severe dysplasia/carcinoma in situ . After that, they may be differentiated again toward keratinization (38). In this step, apoptotic figures are expected to decrease in number from the middle layer, and instead apoptosis may be induced by a crowding condition in the lower layer of severe dysplasia/carcinoma in situ , which was observed in the present study as well as in the previous studies (5, 9).…”
Section: Discussionmentioning
confidence: 99%
“…The morphological differentiation of keratinizing well-matured and differentiated cancer tissue and normal mucosa is very difficult. Although CIS (WHO) in the oral mucosa is an accepted concept, there are very few reported cases, and almost all of these show keratinizing matured and differentiated histopathological features [10,11,42,45,[84][85][86]. As mentioned above, the most common and distinct histological variations are recognized as differentiated and basaloid types, with transitional variations between them in many cases.…”
Section: Pathological Findings Of Oin/cis (Jsop)mentioning
confidence: 97%